The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1152/jn.00234.2003
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of the Tuning of Fly Visual Interneurons to Rotatory Optic Flow

Abstract: The sophisticated receptive field organization of motion-sensitive tangential cells in the visual system of the blowfly Calliphora vicina matches the structure of particular optic flow fields. Hypotheses on the tuning of particular tangential cells to rotatory self-motion are based on local motion measurements. So far, tangential cells have never been tested with global optic flow stimuli. Therefore we measured the responses of an identifiable neuron, the V1 tangential cell, to wide-field motion stimuli mimick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 45 publications
5
40
0
Order By: Relevance
“…There, the responses of VS cells tend to saturate with increasing size of stimulated area (Haag et al, 1992). Furthermore, stimulation of V1 revealed that, unlike DNOVS1, V1 responds almost as strongly to large-field downward motion as to rotational flow fields that perfectly match its receptive field (Karmeier et al, 2003). Thus, a linear response summation in DNOVS1 increases its response selectivity compared with the one of lobula plate cells substantially.…”
Section: Functional Significance Of Rotational Tuningmentioning
confidence: 93%
See 1 more Smart Citation
“…There, the responses of VS cells tend to saturate with increasing size of stimulated area (Haag et al, 1992). Furthermore, stimulation of V1 revealed that, unlike DNOVS1, V1 responds almost as strongly to large-field downward motion as to rotational flow fields that perfectly match its receptive field (Karmeier et al, 2003). Thus, a linear response summation in DNOVS1 increases its response selectivity compared with the one of lobula plate cells substantially.…”
Section: Functional Significance Of Rotational Tuningmentioning
confidence: 93%
“…Per hemisphere, there exist three HS cells (the northern HSN, the equatorial HSE, and the southern HSS cell) and 10 VS cells (VS1-VS10), together covering almost completely the visual space surrounding the animal. LPTCs often have complex receptive fields, with different preferred direction in different parts of the visual field matching the optic flow that occurs during specific flight maneuvers of the fly (Krapp and Hengstenberg, 1996;Krapp et al, 1998;Franz and Krapp, 2000;Karmeier et al, 2003). HS and VS cells are the major output elements of the lobula plate.…”
Section: Introductionmentioning
confidence: 99%
“…The large regional differences in contrast sensitivity and temporal frequency tuning we found, in HSN for example, are not particularly evident in the map of LPD/LMS, and thus highlight the difficulty of predicting responses based solely on this characterization. Indeed, one study (Karmeier et al, 2003) shows that the responses of the V1 cell, a spiking LPTC predicted to be sensitive to pitch-like optic flow, responds strongly to any global motion with a strong frontal downward component (although the preferred rotation axis stays unchanged even if lift translation is combined with rotation). An alternative, but not mutually exclusive, view of LPTC encoding of self motion has recently been proposed, which suggests that HS may encode both rotational and translational information in different frequency bands, although the means flies might use to decode this information is unclear .…”
Section: Matched Filter Hypothesismentioning
confidence: 99%
“…In addition to the columnar input, many tangential cells receive input from other tangential cells (Hausen, 1984;Horstmann et al, 2000;Haag and Borst, 2001, 2005Farrow et al, 2003Farrow et al, , 2005Farrow et al, , 2006Kalb et al, 2006). Together with the directionally selective input from columnar elements, these lobula plate network interactions are responsible for the tangential cell tuning to specific flow fields (Krapp and Hengstenberg, 1996;Krapp et al, 1998;Franz and Krapp, 2000;Karmeier et al, 2003;Cuntz et al, 2007). Although LPTCs have been studied extensively, much less is known about the descending neurons postsynaptic to LPTCs, which project via the cervical connective into the thoracic ganglion.…”
Section: Introductionmentioning
confidence: 99%